Meeting Industry Adaptation during Covid-19 Case Study at PT XYZ - Qoniah, Inas; Asnawi, Yudha Heryawan; Djohar, Setiadi (International Journal Labs, 2023)
The MICE industry is an acronym for Meeting, Incentive, Convention, and Exhibition, which is an industrial activity in the service sector that is synonymous with providing a service. The MICE industry sector, which consists of meetings, incentives, conferences, and exhibitions as well as special events such as cultural, music and sports festivals, during the pandemic when it is carried out virtually or hybrid, the most adaptable is the organization of the meeting and conference sector, according to data released by Kemenparekraf (2021), as many as 65% of meetings are conducted virtually and 61.5% for hybrid meeting formats. The MICE industry in its activities has several financing components such as production value, number of participants, and supporting activities in its implementation that have differences before and after the pandemic, besides that in the meeting itself several components of production costs such as venue costs, production, food and beverage, and accommodation changed completely during the pandemic. PT XYZ adjusted the organization of meetings or meetings during the Covid-19 pandemic, there are challenges in transforming the meeting industry, the right strategy is needed to deal with the problems that occur. This research is expected to be useful for the MICE industry in general, especially the meeting business to formulate strategies to adapt to business transformation towards digital. Furthermore, this research is expected to be useful for academics as a reference for MICE industry business research.